What Does It Mean to Be a Clinical Track Faculty Member in Public Health? A Survey of Clinical Track Faculty Across the United States. (November 2022) - August, Ella; Power, Laura; Youatt, Emily J.; Anderson, Olivia S.
Objectives: The clinical professor track has expanded and reflects a trend toward hiring non–tenure-track faculty in public health; however, little is known about this track. We documented characteristics of clinical faculty at US schools of public health. Methods: We surveyed clinical faculty at Council on Education for Public Health–accredited schools of public health in the United States in 2019, identified via each school's website. We invited faculty (n = 264) who had the word clinical in their title (ie, apparently eligible faculty), had a working email address, and were not authors of this article to provide information about their rank, degree credentials, expectations for teaching, service, research and practice, and promotion criteria at their institution. In addition, we used open-ended responses to explain and contextualize quantitative data. Results: Of 264 apparently eligible faculty surveyed, 88 (33.3%) responded. We included 81 eligible clinical faculty in our final sample, of whom 46 (56.8%) were assistant professors and 72 (88.9%) had a terminal degree; 57 of 80 (71.3%) had an initial contract of ≤2 years or no contract. Most clinical faculty listed service (96.2%), teaching (95.0%), and student advising/mentoring (86.3%) as duties; fewer clinical faculty reported research (55.0%), practice (33.8%), or clinic (7.5%) duties. Only 37.1% of respondents agreed or strongly agreed that promotion policies for clinical track faculty were clear. Conclusions: If most clinical faculty are at the lowest academic rank, with short contracts and unclear expectations, it will be difficult for clinical faculty to advance and challenging for schools of public health to benefit from this track. Clear institutional expectations for scope of work and promotion may enhance the contribution of clinical faculty to schools of public health and help define this track.